Shexiang Baoxin Pills Inhibited Proliferation and Migration of Human Coronary Artery Smooth Muscle Cells via PI3K/AKT/mTOR Pathway - Hua, Lei; Zhou, Yaqing; Hou, Can; Chen, Jiaxin; Wang, Yanjun; Zhang, Sheng; Zhou, Hanxiao; He, Shu; Jia, Enzhi (Frontiers in Cardiovascular Medicine, 2021)
Background: Proliferation and migration of smooth muscle cells in the coronary artery contribute to the deterioration of coronary artery disease (CAD). Aim: This research was designed to study the function of Shexiang Baoxin pills (SBPs) on the proliferation and migration of human coronary artery smooth muscle cells (HCASMCs) and their mechanism. Methods: Oxidized low-density lipoprotein (ox-LDL) was applied to stimulate the proliferation and migration of HCASMCs. The function of ox-LDL and SBP on HCASMCs was evidenced by the cell counting kit-8 assay, cell cycle, and Transwell assay. Network pharmacology was employed to predict the potential targets and pathways of SBP on CAD. Western blot assay and molecular docking were conducted to validate the potential targets and pathways. Results: The current research revealed that 2.5 mg/L SBP significantly inhibited the proliferation and migration of HCASMCs. Besides, network pharmacology revealed 11 candidate targets. Molecular docking and Western blot assay validated that the activation of the top 2 targets STAT3 and MAPK14 was associated with the inhibition of HCASMCs. Moreover, the Western blot assay also detected that HCASMCs treated with ox-LDL promoted the phosphorylation of the PI3K/AKT/mTOR pathway, and SBP inhibited the activation of the PI3K/AKT/mTOR pathway in HCASMCs stimulated by ox-LDL. Conclusion: This study demonstrated that the treatment of CAD using SBP may result from the suppression of the proliferation and migration of HCASMCs. The mechanism of this function partly resulted from relieving the phosphorylation of targets STAT3 and MAPK14 and the PI3K/AKT/mTOR pathway. This study enhanced our comprehension of SBP and provides new targets for the treatment of CAD.